2023
DOI: 10.1021/acscatal.3c00889
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mechanism and Microkinetic Model-Driven Rational Screening of 3N-Modulated Single-Atom Catalysts for Propane Dehydrogenation

Abstract: Direct propane dehydrogenation (PDH) is an economically competitive and environmentally friendly industrial scheme used to produce propylene. Beyond the traditional Pt or Cr oxide catalyst, in this study, we focus on 3N-coordinated transition-metal single-atom catalysts confined within graphene (TM1-N3/C) for PDH due to their open coordination configuration with tunable capability for C–H activation. A total of 29 TM1-N3/C catalysts, covering the majority of 3d–5d transition metals, are systematically screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…In addition, it is reasonable to expect that DPD motifs with the formation energies ( E f ) < 0 eV are experimentally accessible. As summarized in Figure S1c and Table S2, the Δ E b and E f of all DPD configurations are comparable to or even more negative than those of single-atom catalysts ,, and dual-atom catalysts, , where some widely discussed single-atom alloys have been implemented to various reactions operating at temperatures above 500 °C. In this regard, the negative Δ E b and extremely high diffusion barriers of isolated metal atoms could preserve the original single atom sites and prevent metal aggregation on these DPD motifs.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, it is reasonable to expect that DPD motifs with the formation energies ( E f ) < 0 eV are experimentally accessible. As summarized in Figure S1c and Table S2, the Δ E b and E f of all DPD configurations are comparable to or even more negative than those of single-atom catalysts ,, and dual-atom catalysts, , where some widely discussed single-atom alloys have been implemented to various reactions operating at temperatures above 500 °C. In this regard, the negative Δ E b and extremely high diffusion barriers of isolated metal atoms could preserve the original single atom sites and prevent metal aggregation on these DPD motifs.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure S5b, the energy difference between the initial state and the final state along the diffusion pathway is approximately equivalent to the kinetic barrier through the CNEB calculations, which was adopted to estimate the leaching barrier of metal atoms. Here, the threshold for the energy barrier was set as high as 3.30 eV so that an atom can cross at 900 K . Based on this criterion, it is observed that surface diffusions of metal atoms all have much higher barriers (above 6.30 eV) than the threshold, suggesting that the investigated DPD motifs are highly resistant toward metal leaching and thus kinetically stable even at 900 K (as listed in Table S2 and a more intuitive histogram as shown in Figure S5c).…”
Section: Resultsmentioning
confidence: 99%
“…Metal-anchored single atom catalysts (SACs) based on nitrogen-doped carbon (C-N-M) have surfaced as promising electrocatalysts for the CO 2 reduction reaction (CO 2 RR). 8–10 Despite the recent attention, the genuine catalytically active site of these materials remains disputed, mainly due to the impact of reaction conditions. External factors, such as axial oxygen atoms, have been reported to profoundly influence the catalytic activity of metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Fortunately, single-atom catalysts (SACs) have provided a promising solution to the above problem by exploiting their locally isolated active sites, which can break the strong di-s bond adsorption mode. 2,3,8 In addition, the activity and stability of SACs can also be tuned by changing the single metal atom, [9][10][11] which provides broad space for screening efficient catalysts for PDH. As an earth-abundant and stable twodimensional material, MoS 2 has been widely used as a substrate for SACs in numerous catalytic systems.…”
Section: Introductionmentioning
confidence: 99%